Carbon export in the naturally iron-fertilized Kerguelen area of the Southern Ocean based on the 234Th approach - F. Planchon (Biogeosciences, 2015)
This study examined upper-ocean particulate organic carbon (POC) export using the 234Th approach as part of the second KErguelen Ocean and Plateau compared Study expedition (KEOPS2). Our aim was to characterize the spatial and the temporal variability of POC export during austral spring (October–November 2011) in the Fe-fertilized area of the Kerguelen Plateau region. POC export fluxes were estimated at high productivity sites over and downstream of the plateau and compared to a high-nutrient low-chlorophyll (HNLC) area upstream of the plateau in order to assess the impact of iron-induced productivity on the vertical export of carbon. Deficits in 234Th activities were observed at all stations in surface waters, indicating early scavenging by particles in austral spring. 234Th export was lowest at the reference station R-2 and highest in the recirculation region (E stations) where a pseudo-Lagrangian survey was conducted. In comparison 234Th export over the central plateau and north of the polar front (PF) was relatively limited throughout the survey. However, the 234Th results support that Fe fertilization increased particle export in all iron-fertilized waters. The impact was greatest in the recirculation feature (3–4 fold at 200 m depth, relative to the reference station), but more moderate over the central Kerguelen Plateau and in the northern plume of the Kerguelen bloom (~2-fold at 200 m depth). The C : Th ratio of large (>53 μm) potentially sinking particles collected via sequential filtration using in situ pumping (ISP) systems was used to convert the 234Th flux into a POC export flux. The C : Th ratios of sinking particles were highly variable (3.1 ± 0.1 to 10.5 ± 0.2 μmol dpm−1) with no clear site-related trend, despite the variety of ecosystem responses in the fertilized regions. C : Th ratios showed a decreasing trend between 100 and 200 m depth suggesting preferential carbon loss relative to 234Th possibly due to heterotrophic degradation and/or grazing activity. C : Th ratios of sinking particles sampled with drifting sediment traps in most cases showed very good agreement with ratios for particles collected via ISP deployments (>53 μm particles). Carbon export production varied between 3.5 ± 0.9 and 11.8 ± 1.3 mmol m−2 d−1 from the upper 100 m and between 1.8 ± 0.9 and 8.2 ± 0.9 mmol m−2 d−1 from the upper 200 m. The highest export production was found inside the PF meander with a range of 5.3 ± 1.0 to 11.8 ± 1.1 mmol m−2 d−1 over the 19-day survey period. The impact of Fe fertilization is highest inside the PF meander with 2.9–4.5-fold higher carbon flux at 200 m depth in comparison to the HNLC control station. The impact of Fe fertilization was significantly less over the central plateau (stations A3 and E-4W) and in the northern branch of the bloom (station F-L) with 1.6–2.0-fold higher carbon flux compared to the reference station R. Export efficiencies (ratio of export to primary production and ratio of export to new production) were particularly variable with relatively high values in the recirculation feature (6 to 27 %, respectively) and low values (1 to 5 %, respectively) over the central plateau (station A3) and north of the PF (station F-L), indicating spring biomass accumulation. Comparison with KEOPS1 results indicated that carbon export production is much lower during the onset of the bloom in austral spring than during the peak and declining phases in late summer.